The role of DNA hydroxymethylation and TET enzymes in placental development and pregnancy outcome - Sara Vasconcelos; Carla Caniçais; Susana M. Chuva de Sousa Lopes; C. Joana Marques; Sofia Dória (Clinical Epigenetics, 2023)
Abstract The placenta is a temporary organ that is essential for supporting mammalian embryo and fetal development. Understanding the molecular mechanisms underlying trophoblast differentiation and placental function may contribute to improving the diagnosis and treatment of obstetric complications. Epigenetics plays a significant role in the regulation of gene expression, particularly at imprinted genes, which are fundamental in the control of placental development. The Ten-Eleven-Translocation enzymes are part of the epigenetic machinery, converting 5-methylcytosine (5mC) into 5-hydroxymethylcytosine (5hmC). DNA hydroxymethylation is thought to act as an intermediate in the DNA demethylation mechanism and potentially be a stable and functionally relevant epigenetic mark on its own. The role of DNA hydroxymethylation during differentiation and development of the placenta is not fully understood but increasing knowledge in this field will help to evaluate its potential role in pregnancy complications. This review focuses on DNA hydroxymethylation and its epigenetic regulators in human and mouse placental development and function. Additionally, we address 5hmC in the context of genomic imprinting mechanism and in pregnancy complications, such as intrauterine growth restriction, preeclampsia and pregnancy loss. The cumulative findings show that DNA hydroxymethylation might be important for the control of gene expression in the placenta and suggest a dynamic role in the differentiation of trophoblast cell types during gestation.